Pelatihan Pertolongan Pertama Kecelakaan terhadap Pengetahuan tentang Luka dan Perdarahan Siswa Madrasah Aliyah Swasta di Kota Samarinda - Milkhatun, Milkhatun; Wulandari, Tri; Rizal, Alfi Ari Fakhrur (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2025)
Background: : Training in schools on First Aid in Wounds and Bleeding is intended not only for teachers, but also given to students or all residents in the school environment and this first aid is needed in various emergencies such as injuries and accidents both at home, on the road, at school, and other places. For helpers who lack sufficient knowledge and motivation, tend to avoid helping victims and doing help without being equipped with knowledge will result in fatal conditions in victims and death can occur. Therefore, students' lack of knowledge about first aid in wounds and bleeding can be overcome by providing counseling and training that aims to increase knowledge, and motivation to become better and more knowledgeable in providing first aid in accidents. Objective: To determine the effect of accident first aid training on injuries and bleeding on students' knowledge at MAS Miftahul Ulum Anggana. Methods: The research design used in this study was pre-experimental with one-group pretest-posttest design. Results: Results obtained before being given health education average pre-test and post-test scores of 11.89 with std deviation of 1,323 while scores after being given health education average pre-test and post-test of 13.14 with a standard deviation of 1,287, this indicates an increase in student knowledge in filling out questionnaires before and after being given health education. Conclusion: students' lack of knowledge about first aid in wounds and bleeding can be overcome by providing counseling and training that aims to increase knowledge, and motivation to become better and more knowledgeable in providing first aid in accidents